KINERJA DAN KAPABILITAS USAHA JASA KONSTRUKSI KECIL DI JAWA TIMUR TERHADAP REGULASI KONSTRUKSI BERKELANJUTAN - Choir, Moch.; Sebayang, Nusa; Wijayaningtyas, Maranatha (Pascasarjana Teknik Sipil Institut Teknologi Nasional Malang, 2024)
The construction sector is important in Indonesia's economic and social development. With the increasing awareness of the importance of sustainability, the implementation of sustainable construction principles has become a must. On the other hand, small-qualified construction service businesses face various challenges in meeting strict regulations and adapting to sustainable practices. This study aims to analyze the performance and capabilities of sustainable construction service businesses in small-qualified contractors in East Java against the implementation of sustainable construction service business regulations. The research method used is a qualitative method. Analysis of the relationship between performance and regulations is carried out on related indicators, namely construction service productivity, project quality, finance, work safety and security and sustainability. By distributing questionnaires to 100 respondents who are members of the East Java Gapeksindo association with small qualifications. The results of the study indicate that there have been efforts to implement the concept of sustainable development in construction projects. The concept of sustainable development can be applied if all related parties understand the principles and regulations that apply.